Intercomparison of pyranometers for distributed measurement system - Michal Krawczynski; Matthias Strobel; Ralph Gottschalg (2009)
Irradiance is one of the most important parameter measured by PV monitoring systems. Its value is needed to estimate reference yield (YR) and after then performance ratio index (PR). Uncertainty convolved with irradiance measurements has a strong influence on final monitoring quality. This paper presents intercomparison test of ten CMP11 pyranometers which will then be used for the measurement of PV systems distributed across two continents and four countries. Measurements were taken under different installation conditions (horizontal, inplane). Ten CV2 ventilation units were used as a part of system improvements. Finally pyranometers data were combined with EKO MS700 spectral measurements to evaluate spectral variations.